'Signpost' – an innovative online solution to mapping resources to curriculum competences. (4th April 2011) - Prince, N J; Ross, J G; Fertleman, C R; Watson, M
Abstract : Aim: Paediatric training is in a period of flux. A move away from the more traditional apprenticeship model to one defined by complex curricula has coincided with a decrease in working hours and an increase in the variety of learning resources. It has become increasingly important to both remain up to date with the changing educational landscape and to seek innovative resources to support training. Our aim was to fill this gap with a bespoke on-line tool to 'signpost' information and resources. Methods: A group of trainers and trainees from our regional School of Paediatrics developed a model based on the educational literature and feedback from trainers and trainees. Software development was undertaken by Deanery staff. Results: We identified the need for an online curriculum map and also a portal to a blend of learning resources mapped to specific competences. Five key areas were identified: People Places Timetables Appraisal and assessment Learning opportunities Each area was developed as part of an easy-to-use graphical website interface providing both information and links to key local, regional and national training resources. Learning opportunities were mapped using our innovative 'Signpost Tool' to enable users to browse the paediatric curriculum and identify a variety of resources which facilitate achieving specific competences. These include e-learning, face to face courses and ideas for innovative training in the workplace. Importantly, all users can write reviews, give a star rating and add resources, creating an open, dynamic, user-driven tool. At launch 300 'signposted' resources were provided and early user feedback indicates a high level of 'buy-in' from trainers and trainees. Based on current growth, we anticipate over 500 resources to be 'signposted' within the first 6 months. Conclusion: Curriculum mapping provides clarity and demonstrates links between learning opportunities and the curriculum. Signpost achieves this and, additionally, provides a portal for all users to contribute quality resources in real-time. We believe Signpost is a nationally applicable tool and hope to explore opportunities beyond our own School.